Da'wah Strategy for Religious Figures in Kedokanbunder Wetan Village, Kedokan Bunder District, Indramayu Regency - Fitria Amalin Christia ‘Nisa; Didik Himmawan (Konsultan Jurnal Ilmiah Indonesia, 2024)
This paper aims to examine the Da'wah Strategy of Religious Figures in Kedokanbunder Wetan Village, Kedokan Bunder District, Indramayu Regency. The research uses qualitative research as an effort to explain narratively what happens in the field. Data collection uses documentation and library techniques. The data collection technique in this research uses observation and documentation techniques. Then draw conclusions from the findings in this research. The results of this research are that if a preacher wants to be successful in preaching, he must master communication skills, approach skills, and of course master the 6 principles of da'wah, namely Qaulan Sadida (correct speech), Qaulan Baligha (targeted speech), Qaulan Ma'rufa (good speech), Qaulan Karima (honoring speech), Qaulan Layina (gentle speech), and finally there is Qaulan Maysura (easily understood speech). And of course the aspect that must be mastered is an understanding of religious theories. If everything has been mastered then a person will be successful in preaching.